IMPLEMENTATION OF PROGRAM MODEL OF PATTERN RECOGNITION OF THE HUMAN - Вечур, Александр Владимирович; Васильев, Артем Геннадьевич (Eastern-European Journal of Enterprise Technologies, 2010)
The article describes the study and formulated the principles of recognition of human facial image. Describes and analyzes the architecture for the implementation of recognition of human facial image. Examples of the results.